Solid-Phase Mediated Methodology to Incorporate Drug into Intermolecular Spaces of Cyclodextrin Columns in Polyethylene Glycol/Cyclodextrin-Polypseudorotaxanes by Cogrinding and Subsequent Heating - Marina Ogawa (2018)
© 2017 American Chemical Society. In this study, a new preparation method was developed to obtain drug/(polyethylene glycol/cyclodextrin-polypseudorotaxane (PEG/CD-PPRX)) complexes in which drugs were incorporated into the intermolecular spaces of CD columns in PEG/CD-PPRXs. This method was solid-phase mediated and used cogrinding and subsequent heating. Guest drug and CD in PEG/CD-PPRX were amorphized by cogrinding, and then crystallization of CD was promoted by subsequent heating. A previously reported sealed-heating method using the gas phase was not applicable for poorly sublimated and thermally unstable drugs such as piroxicam (PXC) and hydrocortisone, whereas this new method allowed these drugs to be incorporated into the intermolecular spaces of γ-CD columns. Furthermore, salicylic acid (SA) and salicylamide were successfully incorporated into the intermolecular spaces of CD columns using α-CD instead of γ-CD. Powder X-ray diffraction and solution-state1H nuclear magnetic resonance measurements revealed that complexation followed the stoichiometric rule and that the size of the guest drug determined whether complexation occurred. Accurate control of preparation conditions (temperature and water content) was required to obtain complexes with high CD crystallinity. Changes in the molecular state and mobility of each component during the formation process of the PXC/(PEG/γ-CD-PPRX) and SA/(PEG/α-CD-PPRX) complexes were evaluated using solid-state NMR measurements. Finally, dissolution enhancement and sublimation suppression of SA in the SA/(PEG/α-CD-PPRX) complex were demonstrated.